Metabolic reprogramming: the central mechanism driving inflammatory polarization in rheumatoid arthritis and the regulatory role of traditional Chinese medicine - Wen, Jianting; Liu, Jian; Wan, Lei; Wang, Fanfan; Li, Yang (Frontiers in Immunology, 2025)
Rheumatoid arthritis (RA) is characterized by high morbidity, disability, and mortality rates and is intricately linked to metabolic reprogramming that governs immune cell dysfunction and inflammatory polarization, thereby driving RA pathogenesis. This review systematically explored the impact of metabolic dysregulation (especially in glucose, lipid, mitochondrial, and glutamine metabolism) on shaping the inflammatory microenvironment of RA. Key metabolic axes included aerobic glycolysis (the Warburg effect), de novo fatty acid (FA) synthesis, mitochondrial bioenergetic dysfunction, and glutaminolysis. Furthermore, the review highlighted the therapeutic potential of traditional Chinese medicine (TCM) in modulating these metabolic pathways to attenuate pro-inflammatory responses and ameliorate RA progression. Through regulation of metabolic enzymes, TCM demonstrated multi-faceted efficacy in restoring metabolic homeostasis and inhibiting pathological inflammation. This review underscored that metabolic reprogramming was pivotal for identifying novel therapeutic targets; our results may provide a scientific foundation for integrating TCM into RA management strategies. These findings advocated for further exploration of metabolism-centered interventions to develop precision therapies for RA.